Understanding the Impact of Neighborhood Churn on Educational Trajectories: A Sibling Study Approach - Weir, Katie (International Journal of Population Data Science, 2025)
Neighbourhood stability is a critical yet under-explored determinant of educational outcomes. Existing research highlights how concentrated deprivation and social disorganisation shape life chances, but the role of neighbourhood churn—the rate at which populations cycle through an area—remains theorised. This study employs a sibling comparison design using Understanding Society (UKHLS) data, Census data and Residential Mobility data to assess the long-term effects of exposure to high-turnover neighbourhoods on educational attainment at ages 16 and 26. By leveraging within-family variation, the study isolates the effects of instability from broader socio-economic disadvantages, addressing selection bias concerns common in neighbourhood effects research. Drawing on structural theories and social capital frameworks, this study hypothesises that children exposed to greater population flux—particularly during formative school years—will experience weaker local social ties, increased school transitions, and disrupted access to institutional resources, all of which contribute to poorer educational outcomes. Using propensity score matching and longitudinal sibling comparisons, we test whether early-life exposure to high churn neighborhoods has a causal effect on long-term educational trajectories, distinct from static deprivation measures such as the Index of Multiple Deprivation (IMD). Findings contribute to neighbourhood policy debates, challenging assumptions that mobility necessarily equates to social mobility. Instead, our results suggest that high churn environments exacerbate instability for remaining residents, reinforcing inequalities rather than alleviating them. These insights have implications for urban planning, education policy, and interventions targeting children in volatile neighbourhoods.